Subclinical atherosclerosis in patients with relapsing-remitting multiple sclerosis - Omerzu, Tomaž; Magdič, Jožef; Hojs, Radovan; Potočnik, Uroš; Gorenjak, Mario; Fabjan, Tanja Hojs (Wiener Klinische Wochenschrift, 2024)
Summary Background Multiple sclerosis is an inflammatory disorder of the central nervous system. Inflammation may create high susceptibility to subclinical atherosclerosis. The purpose of this study was to compare subclinical atherosclerosis and the role of inflammatory cytokines between the group of patients with relapsing-remitting multiple sclerosis (RRMS) and healthy controls matched for age and sex. Methods The study group consisted of 112 non-diabetic and non-hypertensive RRMS patients treated with disease modifying drugs (DMD) and the control group was composed of 51 healthy subjects. The common carotid artery (CCA) intima media thickness (IMT) was investigated. Serum levels of risk factors for atherosclerosis and inflammatory cytokines were also determined. Results The mean CCA IMT (0.572 ± 0.131 mm vs. 0.571 ± 0.114 mm) did not differ ( p > 0.05) between patients and controls. The RRMS patients’ CCA IMT was significantly correlated with serum interleukin 6 (IL-6) ( p = 0.027), high-sensitivity C-reactive protein (hs-CRP) ( p = 0.027), cystatin C ( p < 0.0005), glucose ( p = 0.031), cholesterol ( p = 0.008), LDL ( p = 0.021), erythrocyte sedimentation rate ( p = 0.001) and triglyceride ( p = 0.018) level. We fitted generalized linear models in order to assess the relationship between CCA IMT and IL‑6 with adjustment for sex and age. The obtained results showed that adjusted for age ( p < 0.001) and sex ( p = 0.048) IL‑6 serum levels statistically significantly ( p = 0.009) predict CCA IMT only in the RRMS group. Conclusion The findings of the present study suggest that when treated with DMD RRMS might not be an independent risk factor for early atherosclerosis presenting with arterial wall thickening; however, the results suggest a significant association of IL‑6 serum levels with CCA IMT only in the RRMS group.